Peradaban Islam Di Nusantara Masa Digital Dan Perkembangan Pendidikannya - Febian Felisiana Yani; Ahsanur Muhammad Rizal; M. Anang Sholikhudin (-, 2026)
Islamic civilization in the archipelago has developed for more than a thousand years with adaptive characteristics and is able to acculturate with local culture  (Abdulrachman,M., 2022).. Entering the digital era, this civilization continues to experience significant transformations, not only in the form of the spread of teachings, but also in its education system  (Amin,M, 2023). Purpose of the article explain to character and dynamics Islamic civilization in the archipelago in facing technological advances, describe the development of Islamic education systems and methods, and identify existing challenges and opportunities. This writing uses a literature review method by collecting and analyzing various relevant reference basis.As a result of the research shows that islam civilization in archipelago is able to adapt to changing times, seen from the usage cyberspace for means preserving or disseminating Islamic values  (Azra,A., 2013)